Interference of mycotoxin binders with ELISA, HPLC and LC-MS/MS analysis of aflatoxins in maize and maize gluten. Issue 3 (3rd March 2020) - Peng, Hong; Chang, Yuwei; Baker, Robert C.; Zhang, Guangtao
ABSTRACT: The aim of this study was to investigate the impact of mycotoxin binders on the determination of aflatoxins in maize and maize gluten using various analytical methods, including ELISA, HPLC and LC-MS/MS. Three types of commercially available mycotoxin binders, yeast cell wall, mineral, and a mixture of mineral and bacterium, were investigated at inclusion levels of 0.1%, 0.2% and 0.4%. The binders were added to maize and maize gluten contaminated with aflatoxins at concentrations between 6.9 and 26.7 μg kg −1 . The samples were analysed and the values were compared with corresponding controls (samples without binders) using ANOVA. The yeast cell wall binder had no significant effect ( p =0.05) on the concentration of aflatoxins measured in either maize or maize gluten at any of the three inclusion levels, regardless of which analytical method was used. The mineral binder and the mixed mineral and bacterium binder had no significant effect ( p =0.05) on the measured aflatoxin concentrations in either maize or maize gluten at any of the three inclusion levels when analysis was conducted using LC-MS/MS. Inclusion of these binders resulted in significant lower ( p <0.01) detection of aflatoxins in both maize and maize gluten when analysis was conducted using ELISA; the effect was dose-dependent. They also resulted in significant lower detection of aflatoxins in maize extracted by methanol/water (70/30 v / v ) ( p <0.0001) and in maize gluten extracted by acetonitrile/water (80/20 v / v ) ( p <0.05) when analysis was conducted using HPLC. However, neither the mineral binder nor the mixed mineral and bacterium binder had significant effects ( p =0.05) on aflatoxin concentrations measured in maize using HPLC, when extracted by acetonitrile/water (80/20 v / v ). The study demonstrated that mycotoxin binders could result in underestimation of the levels of aflatoxin contamination, depending on the nature of the binder, the extraction solvent used in the analytical method, and the composition of tested sample.